(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Asthma is a chronic inflammatory disease of the airways, it results from a combination of genetic predisposition and environmental factors. Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by persistent respiratory symptoms and airflow limitation. Endothelin Converting Enzyme-1 (ECE-1) is an enzyme involved in the activation of endothelin-1 (ET-1), a potent vasoconstrictor and pro-inflammatory peptide. ET-1 plays a significant role in the pathophysiology of both asthma and COPD. Angiotensin-Converting Enzyme (ACE) plays a pivotal role in the renin-angiotensin system, converting angiotensin I to the potent vasoconstrictor angiotensin II, and inactivating bradykinin, a vasodilator. This enzyme is implicated in the pathophysiology of both asthma and COPD. Methods: we performed Case-Control study compressing (n=160) including asthmatic patients (n=40) and COPD patients (n=40) with apparently healthy control subject group (n=80). Results: The mean ± SD age of patients with Asthma were (167.19± 19.66 years in ECE-1), (28.13± 5.12 years in ACE2) and in the Chronic Obstructive Pulmonary Disease were (213.75± 15.27 years in ECE-1), (24.36± 5.25years in ACE2) there was no a significant difference between groups patients. The mean ECE-1 levels with standard deviation (Mean± SD) are 167.19± 19.66 for Asthma, 213.75± 15.27 for COPD, and 101.43± 18.04 for Control. The statistical significance (Pr > F(Model)) is highly significant for Asthma (p < 0.000001), indicating a strong association between Asthma and ECE-1 levels. However, for COPD and Control groups, the p-value is not provided, necessitating further analysis or interpretation to understand the significance of these results. The mean ACE2 levels with standard deviation (Mean± SD) are 28.13± 5.12 for Asthma, 24.36± 5.25 for COPD, and 52.48± 13.36 for Control. The statistical significance based on ANOVA (p < 0.000001) is highly significant for Asthma, suggesting a strong association between Asthma and ACE2 levels. However, for the COPD and Control groups. Conclusion: serum activity of, Endothelin Converting Enzyme-1 a significant increase in patients with Asthma and Chronic Obstructive Pulmonary Disease compared with control, and Angiotensin Converting Enzyme-2 activity decreased in patients with Asthma and Chronic Obstructive Pulmonary Disease compared with control.